Development and Evaluation of a Peptide Heterodimeric Tracer Targeting CXCR4 and Integrin αvβ3 for Pancreatic Cancer Imaging - Yaqun Jiang; Yu Long; Hao Ji; Pengxin Qiao; Qingyao Liu; Xiaotian Xia; Chunxia Qin; Yongxue Zhang; Xiaoli Lan; Yongkang Gai (MDPI AG, 2022)
Nowadays, pancreatic cancer is still a formidable disease to diagnose. The CXC chemokine receptor 4 (CXCR4) and integrin αvβ3 play important roles in tumor development, progression, invasion, and metastasis, which are overexpressed in many types of human cancers. In this study, we developed a heterodimeric tracer 68Ga-yG5-RGD targeting both CXCR4 and integrin αvβ3, and evaluated its feasibility and utility in PET imaging of pancreatic cancer. The 68Ga-yG5-RGD could accumulate in CXCR4/integrin αvβ3 positive BxPC3 tumors in a high concentration and was much higher than that of 68Ga-yG5 (p < 0.001) and 68Ga-RGD (p < 0.001). No increased uptake of 68Ga-yG5-RGD was found in MX-1 tumors (CXCR4/integrin αvβ3, negative). In addition, the uptake of 68Ga-yG5-RGD in BxPC3 was significantly blocked by excess amounts of AMD3100 (an FDA-approved CXCR4 antagonist) and/or unlabeled RGD (p < 0.001), confirming its dual-receptor targeting properties. The ex vivo biodistribution and immunohistochemical results were consistent with the in vivo imaging results. The dual-receptor targeting strategy achieved improved tumor-targeting efficiency and prolonged tumor retention in BxPC3 tumors, suggesting 68Ga-yG5-RGD is a promising tracer for the noninvasive detection of tumors that express either CXCR4 or integrin αvβ3 or both, and therefore may have good prospects for clinical translation.